2018
DOI: 10.1016/s0140-6736(18)30367-2
|View full text |Cite
|
Sign up to set email alerts
|

Definition, causes, and consequences of Hamm (idiom of distress in Arabic) in the Palestinian context: a qualitative study

Abstract: Background Hamm is an Arabic word that is used to express suffering. Idioms of distress are communicated differently in different contexts and cultures. Understanding idioms of distress and symptoms can help in diagnosis and lead to socioculturally sensitive health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Idioms of distress as they emerged in the experts' perceptions indicated the sense of oppression and humiliation that Palestinians experience (Barber et al, 2013(Barber et al, , 2016bLacey, 2011). In contrast, idioms of distress mentioned by authors who studied populations affected by war and political violence in other Arab contexts did not reflect feelings of suffocation and closure (El-Shaarawi, 2012;Hassan et al, 2015;Nasir et al, 2018). For example, El-Shaarawi (2012) reported idioms common among Iraqi refugees in Egypt.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Idioms of distress as they emerged in the experts' perceptions indicated the sense of oppression and humiliation that Palestinians experience (Barber et al, 2013(Barber et al, , 2016bLacey, 2011). In contrast, idioms of distress mentioned by authors who studied populations affected by war and political violence in other Arab contexts did not reflect feelings of suffocation and closure (El-Shaarawi, 2012;Hassan et al, 2015;Nasir et al, 2018). For example, El-Shaarawi (2012) reported idioms common among Iraqi refugees in Egypt.…”
Section: Discussionmentioning
confidence: 96%
“…Other idioms of distress identified in Syria were ana ta'ban (I am tired) and nafsiyti ta'banah (my psyche is tired), indicating emotional exhaustion and fatigue as a result of the prolonged displacement characterizing the Syrian population's human insecurity (Hassan et al, 2015). Nasir et al (2018) found that the Arabic expression Hamm (worry) is a common expression of distress in Gaza. In our study sample, the term Makhnogeen ("we are suffocating"), the plural form of the term Makhnouk (feeling of suffocation), was commonly used to express the collective and social suffering of Palestinians, whereas Iraqi refugees define their suffering using the singular form of the term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation